William Wilberforce : the life of the great anti-slave trade campaigner - Hague, William, 1961- (Orlando : Harcourt, 2007)
A major biography of abolitionist William Wilberforce, the man who fought for twenty years to abolish the Atlantic slave trade.
"First published in Great Britain by HarperCollinsPublishers"--T.p. verso.
Includes bibliographical references (p. 543-555) and index.
Keywords: Wilberforce, William, -- 1759-1833.; Legislators -- Great Britain -- Biography; Abolitionists -- Great Britain -- Biography; Philanthropists -- Great Britain -- Biography; Great Britain -- Politics and government -- 1760-1820.; Great Britain -- Politics and government -- 1820-1830.